Re-introduction of India ink testing as a low-cost laboratory diagnostic for cryptococcosis among HIV infected patients in Southern Mozambique: An implementation research protocol - José C. Langa; Mohsin Sidat; Jahit Sacarlal; Troy D. Moon (PLoS ONE, 2025)
Laboratory diagnosis for cryptococcal disease among HIV-infected patients remains a challenge in most low- and middle-income countries (LMIC). Difficulties with sustained access to cryptococcal rapid tests is cited as a major barrier to the routine screening for cryptococcus in many LMIC. Thus, clinicians in these countries often resort to empirical treatment based solely on clinical suspicion of cryptococcosis. To address this challenge, we aim to evaluate the re-introduction of India ink testing for diagnosis of cryptococcosis among HIV-infected patients in southern Mozambique. India ink testing was historically a common first choice, low-cost, laboratory diagnostic tool for cryptococcal infection. This study uses implementation science methods framed by the Dynamic Adaption Process (DAP) and the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) conceptual frameworks to develop a multi-phase, stepped-wedged trial using mixed-methods approaches. The study will be conducted in six hospitals from southern Mozambique over a period of 15 months and will include the following phases: pre-implementation (baseline assessment), Adaptation-implementation (gradual introduction of the intervention), and post-implementation (post-intervention assessment). This study aims to promote the use of India Ink staining as a cheap and readily available tool for cryptococcosis diagnosis in southern Mozambique. Lessons learned in this study may be important to inform approaches to overcome the existing challenges in diagnosis of cryptococcosis in many LMICs due unavailability of readily diagnostic tools. Trial registration: ISRCTN11882960, Registered 06 August 2024.